2005
DOI: 10.1002/ptr.1734
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory, analgesic and antiperoxidative efficacy of Barleria lupulina Lindl. extract

Abstract: A study was undertaken to investigate the antiinflammatory efficacy of methanol extract of aerial parts of Barleria lupulina Lindl. [MEBL] (Family: Acanthaceae) in acute and sub-acute inflammation models of albino rats. The MEBL in all the tested dose levels exhibited significant inhibition of carrageenin and serotonin induced paw oedema volumes when compared with the untreated (control) group. The MEBL also exerted a significant reduction in granuloma weight in the cotton pellet induced granuloma model. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…An initial phase during the first 1.5 h is caused by the release of histamine and serotonin [20]. The second phase involves the release of bradykinin from 1.5 h to 2.5 h, whilst the third phase involves the release of prostaglandins and that occurs from 2.5 h to 6.0 h after albumin injection [21]. The current study lasted for only 120 min due to rapid resolution of inflammation.…”
Section: Anti-inflammatory Activitymentioning
confidence: 96%
“…An initial phase during the first 1.5 h is caused by the release of histamine and serotonin [20]. The second phase involves the release of bradykinin from 1.5 h to 2.5 h, whilst the third phase involves the release of prostaglandins and that occurs from 2.5 h to 6.0 h after albumin injection [21]. The current study lasted for only 120 min due to rapid resolution of inflammation.…”
Section: Anti-inflammatory Activitymentioning
confidence: 96%
“…Carrageenan is phlogistic agent which induced edema develops by mediators in two phases, so inflammation produced by carrageenan has a biphasic effect. The first phase is due to release of mediators such as histamine and serotonin occurs within 0-2 hrs [35] and the second accelerating phase edema is attributed to bradykinins and PG release (>4 th hr) [36]. The results of the present study showed that methanol extract of P. major significantly inhibited the formation of the rat paw edema in the early and late phases.…”
Section: In Vivo Anti-inflammatory Activitymentioning
confidence: 48%
“…The local injection of carrageenan-induced inflammatory process in the rat involves three phases through sequential release of several mediators. An initial phase, during the first 1.5 h, is caused by the release of histamine and serotonin [22], a second phase is mediated by bradykinin from 1.5 to 2.5 h and finally, a third phase, the mediator of which is suspected to be prostaglandins occurs from 2.5 to 6 h after carrageenan injection [23]. This third phase appears to be the most interesting phase in terms of inflammatory processes.…”
Section: Discussionmentioning
confidence: 96%